Pathophysiological Role of Caveolae in Hypertension - Lian, Xiaoming; Matthaeus, Claudia; Kaßmann, Mario; Daumke, Oliver; Gollasch, Maik (Frontiers in Medicine, 2019)
Caveolae, flask-shaped cholesterol- and glycosphingolipid-rich membrane microdomains, contain caveolin 1 and several structural proteins, in particular Cavin 1-4, EHD2, pacsin 2, and dynamin-2. Caveolae participate in several physiological processes like lipid uptake, mechanosensitivity or signaling events and are involved in pathophysiological changes in the cardiovascular system. They serve as a specific membrane platform for a diverse set of signaling molecules like eNOS, and further maintain vascular homeostasis. Lack of caveolins causes the complete loss of caveolae, induces vascular disorders, endothelial dysfunction, impaired myogenic tone and alters numerous cellular processes, which are all contributing to an increased risk for hypertension. This brief review describes our current knowledge on caveolae in vasculature, with special focus on their pathophysiological role in hypertension.